Problem of the Foundations of Gnoseology: The Tradition of R. Descartes and I. Kant - Skersytė, Jūratė (Problemos, 1989)
An attempt is made to explicate the methodological content of the gnoseological critique of ontology in the philosophy of R. Descartes and I. Kant. The peculiarity of I. Kant’s critical approach as well as his inference about the opposition between philosophy and science is considered as a consequence of more consistent realisation of R. Descartes’ methodological approach.